2016
DOI: 10.1074/jbc.m115.702555
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct Requirements for 5′-Monophosphate-assisted RNA Cleavage by Escherichia coli RNase E and RNase G

Abstract: RNase E and RNase G are homologous endonucleases that play important roles in RNA processing and decay in Escherichia coli and related bacterial species. Rapid mRNA degradation is facilitated by the preference of both enzymes for decay intermediates whose 5 end is monophosphorylated. In this report we identify key characteristics of RNA that influence the rate of 5-monophosphate-assisted cleavage by these two ribonucleases. In vitro, both require at least two and prefer three or more unpaired 5-terminal nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…A processed ermBL EF -ermB mRNA intermediate was detected at a site one nucleotide downstream of the predicted core SD sequence (69). Close inspection showed that the sequences flanking the cleavage site conspicuously resembled the previously reported RNase E target sequence ([A/G]AUU[A/U/C] (4547). RNase E cleavage sites often occur in A/U-rich single-stranded regions; however, no definitive consensus has yet been identified (66, 70).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…A processed ermBL EF -ermB mRNA intermediate was detected at a site one nucleotide downstream of the predicted core SD sequence (69). Close inspection showed that the sequences flanking the cleavage site conspicuously resembled the previously reported RNase E target sequence ([A/G]AUU[A/U/C] (4547). RNase E cleavage sites often occur in A/U-rich single-stranded regions; however, no definitive consensus has yet been identified (66, 70).…”
Section: Resultssupporting
confidence: 53%
“…Consistent with relevant clinical studies, we found that cells bearing truncated ErmBL (and consequently impaired in ribosome stalling) remain highly resistant via a previously underappreciated mechanism by which the antibiotic promotes the stability of ermB mRNA. We found that ermBL-ermB mRNA is more susceptible to RNase in the absence of ERY and that the nucleolytic site lies immediately downstream of the ermBL SD at a region coinciding with the reported consensus sequence of some RNase E substrates (4547). Finally, we found that other cationic ribosome inhibitors, regardless of their ability to elicit ribosome stalling, can increase the mRNA abundance of a specific group of genes, most likely by enhancing mRNA stability.…”
Section: Introductionmentioning
confidence: 61%
“…RNase E is a major bacterial enzyme involved in RNA decay. It can access its RNA substrates either via internal AU-rich binding sites or, more efficiently, through interaction with the 5'-terminal monophosphate groups (Richards & Belasco 2016). It has been proposed that the MicC sRNA, by binding to the ompD mRNA, recruits RNase E to induce rapid mRNA degradation (Pfeiffer et al, 2009;Bandyra et al, 2012).…”
Section: Regulation By Srnas Binding Deeply In the Coding Sequencementioning
confidence: 99%
“…The Hfq protein also plays a role in protecting bound sRNA molecules from degradation before they pair with their mRNA targets (Saramago et al, 2014). RNase E is a major enzyme responsible for RNA degradation and processing in E. coli and displays specificity towards single-stranded AU-rich sequences and 5'-monophosphorylated substrates (Saramago et al, 2014;Frohlich et al, 2016;Richards & Belasco, 2016). However, other RNases are also involved in regulation exerted by sRNAs (Andrade et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other independent endoribonucleases contribute to the turnover of mRNAs, as RNase G, RNase I and RNase III 10 12 . E. coli RNase G is an endonuclease possessing ∼50% sequence similarity to the RNase E catalytic region and overlapping, but not identical, cleavage specificity 13 – 15 . RNase G is found in Gram-negative pathogen microorganisms such as Klebsiella pneumoniae , Acinetobacter baumannii , Pseudomonas aeruginosa , Enterobacter cloacae and E. coli , and is not an essential protein 16 .…”
Section: Introductionmentioning
confidence: 99%